Animals in China - Cao, Deborah. author. aut Link
XIV, 216 p.
Keywords: Just as China is called the world factory for manufactured goods, it is also a world factory for manufactured animal cruelty in a new phenomenon of globalized animal cruelty. Animals in China examines animal protection in China in its legal, social and cultural contexts.